Pengaruh tekanan ketaatan, independensi, kompleksitas tugas dan etika terhadap audit judgment - Rachmat Handani; Zirman '; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aimed to examine the effect of obedience pressure,independence, task complexity and ethics toward audit judgment. This research was carried out at Pekanbaru and Padang. The population in this research were Public Accountant Office in Pekanbaru and Padang as much 12 Offices. The sample in this research was senior and junior auditor working in Public Accountant Offices in Pekanbaru and Padang. Data collected by questionnaire distributed directly to the auditor as much 60 questionnaires and only 48 questionnaires replayed. Data analysis used multiple linear regression method with SPSS version 17.The result of this research showed that obedience pressure significantlyaffect audit judgment, independence significantly affect audit judgment and ethics significantly affect audit judgment, but task complexity didn’t significantly affect audit judgment taken by auditor.Key word : Obedience Pressure, Independence, Task Complexity, Ethics, Audit Judgment